2018
DOI: 10.2478/pjst-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Level of Motor Preparation of Professional Soccer Players in Training

Abstract: Introduction. Since the competition period has been prolonged in modern football, it is important to know if a shortened preparatory phase is enough to improve motor fitness preparation. This study analysed the changes in the level of physical fitness in second-league soccer players with respect to training conducted during the preparatory period. Material and methods. Speed (5-m and 30-m sprint), endurance (progressive test), and power (Counter Movement Jump) were tested in 21 players at the beginning and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Pozzo et al (30) have reported similarities between these exercises and throwing sports in athletics about the movement of the athlete's center of gravity as well as the force and neuromuscular stimulation generated. The clean and its derivatives are used in training in judo (37), rowing (22), wrestling (25), and team sports (1,14,15,(17)(18)(19)32), as well as the training of adolescent male athletes (27). The growing popularity of CrossFit has recently caused an increased interest in exercises used in Olympic weightlifting training.…”
Section: Introductionmentioning
confidence: 99%
“…Pozzo et al (30) have reported similarities between these exercises and throwing sports in athletics about the movement of the athlete's center of gravity as well as the force and neuromuscular stimulation generated. The clean and its derivatives are used in training in judo (37), rowing (22), wrestling (25), and team sports (1,14,15,(17)(18)(19)32), as well as the training of adolescent male athletes (27). The growing popularity of CrossFit has recently caused an increased interest in exercises used in Olympic weightlifting training.…”
Section: Introductionmentioning
confidence: 99%
“…During the 90 minutes of the game, soccer players spend most of the time performing low to moderate intensity activities such as walking or jogging, and energy is mainly produced by aerobic metabolism [4,5]. Therefore, elite level soccer requires well-developed aerobic fitness [6,7,8].…”
Section: Introductionmentioning
confidence: 99%